Pentingnya Pembelajaran Bahasa Inggris di Usia Dini - Susilo Budi Darmawan; Adhinta Putra Ajie; Saniyyah Difta Pratiwi (Dharmakayana, 2024)
English language learning at an early age plays an important role in children's cognitive, social and emotional development. This article evaluates the impact of teaching English through varied and interactive methods, such as educational games, songs, and creative activities, conducted on weekends. Based on observation and documentation, it was found that these methods significantly improved children's understanding of English vocabulary and structures, as well as strengthened their thinking, memory and problem-solving skills. In addition to cognitive benefits, English language teaching also supports the development of social skills by improving children's communication and collaboration abilities. Despite challenges such as the need for more diverse materials and adjustments to methods, adaptive approaches and the use of technology can improve learning effectiveness. The findings emphasize the importance of English language learning at an early age to prepare children for a connected global environment.